Relationship between urban mobility and quality of life based on the social representations of older people in a medium-sized city (PerCursos, 2023)
Population aging and urbanization are two growing global phenomena. This scenario requires changes that involve the urban mobility experienced by older individuals. Therefore, this study aimed to analyze the relationship between urban mobility and quality of life based on the social representations of older people. This is a qualitative research that conducted documentary research and semi-structured interviews. Eleven older individuals, who are members of the SUPERidade Project of the Social Assistance Department of the city of Chapecó, State of Santa Catarina, participated in the study. For the analysis of the information, the technique of thematic content analysis was used, delimited to the category "Urban Mobility and Quality of Life as a Right to the City." Urban mobility enables older individuals to reach desired destinations, access health care and leisure activities, which represent quality of life. The influence of urban space on the mobility of older individuals can promote quality of life and social inclusion, or the opposite, as it enables or restricts opportunities to enjoy what the city offers. It is understood that urban mobility is one of the factors that make up the social determinants of health, given its influence on the access of older individuals to the city. Considering that aging is a progressive, irreversible, and predictable process in the course of life, urban space can be restructured, contributing to the inclusion of older individuals with different degrees of functional capacity in order to promote a more just, democratic, and healthy urban space.
Keywords: urban mobility; mobility of older adults; right to the city; social representations; quality of life